THE RELATIONSHIP BETWEEN DIMENSIONS OF SPORT SERVICE QUALITY AND JOB CREATION RATE IN PRIVATE CLUBS - Saeed Sadeghi Boroujerdi; Kaveh Hasani (Sport Scientific And Practical Aspects, 2025)
In this research, the relationship between dimensions of service quality and job creation rate in Kurdistan province was examined. This research was descriptive-survey and statistical population consisted of private clubs in Kurdistan province that included 191 clubs during implementation of research. Results obtained from study’s hypotheses test using Pearson correlation coefficient showed that: there is meaningful relation between qualities of presented sport service with the rate of job creation in “tangible factors”, “reliability” and “responsiveness” aspects. But, there is no meaningful relation quality of presented sport service with the rate of job creation in “assurance” and “empathy” aspects. Results showed assurance; tangibles, empathy and responsiveness aspects are respectively have highest utility among clubs’ clients and reliability factor aspect has minimum utility among sport service quality aspects. Regression analysis result regarding affective factors’ influence over job creation showed that multiple correlation coefficient of service quality’s five variables (tangibles, reliability, assurance, responsiveness and empathy) with (job creation) variable is equal to 0/65 that based on severity, it is a medium to high correlation.